2018
DOI: 10.3171/2017.8.jns171168
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative monitoring with visual evoked potentials for brain surgeries

Abstract: OBJECTIVEThe goal of this study was to determine the performance of intraoperative visual evoked potentials (VEPs) in detecting visual field changes.METHODSAssessments of VEPs were performed with simultaneous retinal responses by using white light-emitting diodes protected from scialytic microscope lights. The alarm criterion was a reproducible decrease in amplitude of the VEP P100 wave of 20% or more. Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 19 publications
(17 reference statements)
0
25
0
Order By: Relevance
“…A recent study showed that if the criterion for significant FVEP change is decreased to ≥20% amplitude reduction (instead of ≥50%) while using multiple recording sites (O1, O2, and Oz) and white light stimulation, then there may be improved detection of iatrogenic injury resulting in quadrantanopia. 25 The high success rate in this study was mostly related to the use of restrictive filtering, optimal reject window settings, mastoid reference, concomitant ERG recordings, and TIVA anesthesia. 4 In a previous paper, we showed that FVEPs are more reproducible in the presence of low-amplitude EEG than high-amplitude EEG.…”
Section: Discussionmentioning
confidence: 78%
“…A recent study showed that if the criterion for significant FVEP change is decreased to ≥20% amplitude reduction (instead of ≥50%) while using multiple recording sites (O1, O2, and Oz) and white light stimulation, then there may be improved detection of iatrogenic injury resulting in quadrantanopia. 25 The high success rate in this study was mostly related to the use of restrictive filtering, optimal reject window settings, mastoid reference, concomitant ERG recordings, and TIVA anesthesia. 4 In a previous paper, we showed that FVEPs are more reproducible in the presence of low-amplitude EEG than high-amplitude EEG.…”
Section: Discussionmentioning
confidence: 78%
“…We have several limitations to our study. We did not have postoperative visual outcomes, but we argued the correlation of intraoperative monitoring and the outcome had been investigated by other studies,46,1421 and our study did not focus on this topic. We have a relatively small sample size for a deep learning study.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups used a 20% to 50% increase or decrease in amplitude as the criterion 2022. Recent studies also argued the effectiveness of intraoperative VEP monitoring during surgeries that might have the risk of optic injury 46. On the contrary, several studies concluded that this procedure had no predictive value for postoperative prognosis 18,19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study (Gutzwiller et al, 2018) reported that a decrease in amplitude of the VEP P100 wave of 20% correctly identified only 66.7% of cases with any postoperative change.…”
Section: Discussionmentioning
confidence: 99%